Comparison of three mathematical prediction models in patients with a solitary pulmonary nodule - Zhang, Xuan; Yan, Hong-Hong; Lin, Jun-Tao; Wu, Ze-Hua; Liu, Jia; Cao, Xu-Wei; Yang, Xue-Ning (Chinese Journal of Cancer Research; Vol 26, No 6 (December 30, 2014): Chinese Journal of Cancer Research, 2014)
Background: Effective methods for managing patients with solitary pulmonary nodules (SPNs) depend critically on the predictive probability of malignancy. Methods: Between July 2009 and June 2011, data on gender, age, cancer history, tumor familial history, smoking status, tumor location, nodule size, spiculation, calcification, the tumor border, and the final pathological diagnosis were collected retrospectively from 154 surgical patients with an SPN measuring 3-30 mm. Each final diagnosis was compared with the probability calculated by three predicted models—the Mayo, VA, and Peking University (PU) models. The accuracy of each model was assessed using area under the receiver operating characteristics (ROC) and calibration curves. Results: The area under the ROC curve of the PU model [0.800; 95% confidence interval (CI): 0.708-0.891] was higher than that of the Mayo model (0.753; 95% CI: 0.650-0.857) or VA model (0.728; 95% CI: 0.623- 0.833); however, this finding was not statistically significant. To varying degrees, calibration curves showed that all three models overestimated malignancy. Conclusions: The three predicted models have similar accuracy for prediction of SPN malignancy, although the accuracy is not sufficient. For Chinese patients, the PU model may has greater predictive power.